1971
DOI: 10.1042/cs0410563
|View full text |Cite
|
Sign up to set email alerts
|

A Reinvestigation of Methylguanidine Concentrations in Sera from Normal and Uraemic Subjects

Abstract: 1.A cation-exchange-chromatographic method for the determination of methylguanidine in serum is described.2. In ten normal subjects, the mean serum methylguanidine concentration was 0·055 (SE 0'019) mg/ 100 ml and in ten uraemic patients it was 0·175 (SE 0,038) mg/ 100 ml. This difference is significant (P<0·02).3. Recent claims that methylguanidine is present in uraemic serum in much higher concentrations are shown to be due to artifactual conversion of creatinine when methods involving charcoal chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

1974
1974
1986
1986

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 11 publications
(17 reference statements)
0
20
1
1
Order By: Relevance
“…Methyl guanidine decreases the mixed-lym phocyte reaction at 7.5 pg/ml and suppresses it completely at 60 pg/ml [67]. The inhibitory concentration in vitro is within the level measured in uremic serum [69]. These mole cules have been shown to suppress phyto hemagglutinin-induced lymphocyte transfor mation [68].…”
Section: Altered In Vitro Lymphocyte Functionmentioning
confidence: 99%
“…Methyl guanidine decreases the mixed-lym phocyte reaction at 7.5 pg/ml and suppresses it completely at 60 pg/ml [67]. The inhibitory concentration in vitro is within the level measured in uremic serum [69]. These mole cules have been shown to suppress phyto hemagglutinin-induced lymphocyte transfor mation [68].…”
Section: Altered In Vitro Lymphocyte Functionmentioning
confidence: 99%
“…The preferential accumulation of MG in the intracellular fluid compart ment where the enzymatic processes take place is consistent with the present view that uremia is the consequence of enzymatic inhibitions; likewise the observation that MG is efficiently excreted by tubuli of insufficient kidneys [2] is consistent with the observation that the severity of the symptoms is lower in patients on maintenance dialysis when an appreciable residual kid ney function is present [10], All these observations suggest that MG retained in renal failure plays an important part in causing several uremic symptoms; however, in contrast to this opinion, it has recently been stated that the plasma levels found in uremic patients are too low to cause any toxic effect [11]. No direct evidence exists to support this statement, since MG has never been administered to humans, whereas indirect evidence exists suggesting the contrary.…”
Section: Effects O F Metabolites Known To Accumulate In Renal Failurementioning
confidence: 48%
“…This effect can easily be observed in rats [12] at plasma concentrations similar to those measured in uremic patients [1][2][3]6,11,18]. Previous data, while not excluding a proximal site of action, provide some indirect evidence for a distal site of action: in fact, it has been suggested that the amidino group of MG may be responsible for the potassium-spar ing effect which occurs in the distal tubule [12].…”
Section: Introductionmentioning
confidence: 77%
“…The present work has been designed to: (1) identify the renal site of action of MG by the aid of various micropuncture tech niques, and (2) evaluate the possible role of this substance in water and sodium regula tion in uremic patients.…”
Section: Introductionmentioning
confidence: 99%